1989
DOI: 10.1093/carcin/10.4.737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E on survival, glutathione reductase and formation of chromium (V) in Chinese hamster V-79 cells treated with sodium chromate (VI)

Abstract: The effect of vitamin E on cytotoxicity induced by Na2CrO4 was evaluated by colony-forming assay using Chinese hamster V-79 cells. Pre-treatment with alpha-tocopherol succinate (vitamin E) for 24 h prior to exposure to Na2CrO4 resulted in a marked decrease in the cytotoxicity caused by this compound. The reduction of chromate-induced cytotoxicity was observed at all concentrations of Na2CrO4 (5-15 microM), and the protective effect increased with higher concentrations of vitamin E (5-25 microM). The level of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 0 publications
1
60
0
Order By: Relevance
“…As a result, premutant cells are likely to be lost from the chromium-treated populations. It is also difficult to define an effective chromium treatment dosing regime, since chromium compounds are often mutagenic over a very narrow dose range (5,6,18,28). This may be partly related to residual toxicity that could result from trivalent Cr that is trapped within the cells (30).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, premutant cells are likely to be lost from the chromium-treated populations. It is also difficult to define an effective chromium treatment dosing regime, since chromium compounds are often mutagenic over a very narrow dose range (5,6,18,28). This may be partly related to residual toxicity that could result from trivalent Cr that is trapped within the cells (30).…”
Section: Resultsmentioning
confidence: 99%
“…Cr(VI) is a well-established human lung carcinogen and previous studies show that Cr(VI) chromium is most potent in particulate form. Particulate Cr(VI) induces DNA strand breaks, Cr-DNA adducts, Cr-DNA crosslinks and mutation to 6-thioguanine resistance in diploid human fibroblasts [8,[14][15][16][17]12,35,36], however how these lesions are repaired and their relationship to Cr(VI)-induced CIN are uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies utilizing vitamin pretreatments have shown that adducts and crosslinks do not correlate with chromosomal aberrations [16][17][18][19]. DNA single strand breaks are very short-lived after particulate Cr(VI) exposure and thus do not seem like likely candidates for inducing chromosome damage [13].…”
Section: Introductionmentioning
confidence: 99%
“…The tetrahedral anionic conformation of the +6 oxidation state of chromium facilitates active transport into cell systems through the phosphate and sulfate cellular transport systems (8). However, Cr(VI) is not the oxidation state that reacts with DNA, and cellular reduction of Cr(VI) to its stable +3 oxidation state forms a wide variety of intermediate high-valent (+4 and +5) oxidation states of chromium, as well as reductant-specific carbon-, oxygen-, and sulfurbased free radicals (9)(10)(11)(12). Both the high-valent chromium intermediates and free radicals have the potential to cause oxidative DNA damage promoted by Cr(VI).…”
Section: Introductionmentioning
confidence: 99%